Exploration of hotel managers' training evaluation practices and perceptions utilizing Kirkpatrick's and Phillips's models. Issue 2 (2nd April 2016) - Ho, Anh D. D.; Arendt, Susan W.; Zheng, Tianshu; Hanisch, Kathy A.
ABSTRACT: Training is one human resource development practice found in most organizations, however, studies showed that little attention is given to the importance of training evaluation in real life practices. This study is an exploration of the practices and perceptions of hotel managers in training evaluation using Kirkpatrick's and Phillips's models. In-depth interviews were conducted with six hotel managers and paper-based questionnaires were sent out to managers of hotels with more than 30 rooms in a Midwestern state. The findings indicated that hotel managers viewed training evaluation activities as important and observation was rated the most important and the most frequently employed method for managers in evaluating training. The study's findings contribute to the literature by providing researchers with more insights into how hotel managers evaluate their training and what they believed a practical process should possess. It also gives researchers a brief understanding of the perceptions of managers from different hotel sizes.